Electron beam decomposition of CdCl2 (1984)
The e-beam stimulated reaction, CdCl2 (s)----Cd(s) + 2Cl(g), has been studied in cadmium chloride thin films between 303 and 483K using 2-keV electrons. The dose required to make 90-mm-deep holes at 483K is 3 X10-3 Ccm-2. Extrapolated dosing levels of ~6X10-5 C cm-2 are expected. The use of CdCl2 as a positive-type electron resist in a new scheme is proposed. A working model, useful for considering the e-beam stimilated decomposition energetics and mechanism, is briefly discussed.